Can Interactive Approach Improve Reading Comprehension? - tri nuzulia nurhuda (Language-Edu, 2020)
This study used Classroom Action Research. The objective is to enhance students’ reading comprehension for recount text for the eight-year students in MTs Terpadu Ar Roihan by implementing interactive approach. The subjects consist of 26 students. The implementation of interactive approach is directed in two cycles. Each cycle consists of 3 meetings. In first cycle, the researcher implements interactive approach which applies pre-reading, whilst reading and post activity during 3 days which ended with the evaluation of reading comprehension test. Teaching was conducted in four stages; 1) pre activity, 2) pre -reading which focuses in activating the relevant schemata 3) whilst-reading activity which focuses in students’ interaction with the text by reading loud, and it will be ended by reading comprehension test, and 4) post-reading activity for reflection. The students’ mean score is 66. It is under the criteria of success (under 75). The researcher made a second planning by revising the teaching scenario. The difference is a change in the activity. In first cycle, the activity is conducted more individually but in the second cycle working in a group is implemented. The material is also changed. The students’ mean score is 77 in second cycle. It meets the criteria of success.